Effectiveness and feasibility of an interprofessional training program to improve patient safety—A cluster-randomized controlled pilot study - Körner, Mirjam; Dinius, Julia; Ernstmann, Nicole; Heier, Lina; Bergelt, Corinna; Hammer, Antje; Pfisterer-Heise, Stefanie; Kriston, Levente (Frontiers in Psychology, 2023)
Introduction Interprofessional healthcare teams are important actors in improving patient safety. To train these teams, an interprofessional training program (IPTP) with two interventions (eLearning and blended learning) was developed to cover key areas of patient safety using innovative adult learning methods. The aims of this study were to pilot test IPTP regarding its effectiveness and feasibility. The trial was registered with DRKS-ID: DRKS00012818. Methods The design of our study included both a pilot investigation of the effectiveness of the two interventions (eLearning and blended learning) and testing their feasibility (effectiveness-implementation hybrid design). For testing the effectiveness, a multi-center cluster-randomized controlled study with a three-arm design [intervention group 1 (IG1): eLearning vs. intervention group 2 (IG2)]: blended learning (eLearning plus interprofessional in-person training) vs. waiting control group (WCG) and three data collection periods (pre-intervention, 12 weeks post-intervention, and 24 weeks follow-up) was conducted in 39 hospital wards. Linear mixed models were used for the data analysis. The feasibility of IPTP was examined in 10 hospital wards (IG1) and in nine hospital wards (IG2) using questionnaires (formative evaluation) and problem-focused interviews with 10% of the participants in the two intervention groups. The collected data were analyzed in a descriptive exploratory manner. Results Pilot testing of the effectiveness of the two interventions (eLearning and blended learning) showed no consistent differences between groups or a clear pattern in the different outcomes (safety-related behaviors in the fields of teamwork, error management, patient involvement, and subjectively perceived patient safety). Feasibility checks of the interventions showed that participants used eLearning for knowledge activation and self-reflection. However, there were many barriers to participating in eLearning, for example, lack of time or access to computers at the ward. With regard to in-person training, participants stated that the training content sensitized them to patient-safety-related issues in their everyday work, and that awareness of patient safety increased. Discussion Although the interventions were judged to be feasible, no consistent effects were observed. A possible explanation is that the duration of training and the recurrence rate may have been insufficient. Another conceivable explanation would be that participants became more sensitive to patient safety-critical situations due to their knowledge acquired through the IPTP; therefore, their assessment post-intervention was more critical than before. In addition, the participants reported high pre-measurement outcomes. Future studies should examine the evidence of the intervention within a confirmatory study after adapting it based on the results obtained.